A Comparison of Instructional Leadership Models: The Western and Malaysian Perception: Perbandingan model kepimpinan instruksional: Persepsi barat dan Malaysia - Samichan, Aziah; Yunus, Jamal @ Nordin; Awang, Marinah; Beram, Sukor (Management Research Journal, 2021)
Instructional leadership remains relevant even after more than three decades. This situation can be substantiated by the diversity of instructional leadership models resulting from the efforts of western and local scholars. In Malaysia, instructional leadership is mandated in the Malaysian Education Development Plan (PPPM) 2013-2025 that advocates school leaders act as instructional leaders. However, there is a tendency amongst local instructional leaders to make western-model instructional leadership models as the main source of reference, even though there are differences, especially in the environmental and cultural aspects. Thus, this study aims to compare the different elements found in five western instructional leadership models, and four local instructional leadership models from the year 2000 onwards, by using the document analysis method. The results of the literature analysis indicate that based on practices in the Malaysian context, there are elements in the theory that must be improved. It is hoped that this study can help researchers formulate the main elements that must be present in an instructional leadership model. The results of this summary will be used as the basis for consideration in the selection of elements for developing a model of instructional leadership in Malaysian schools.